STUDY TO EVALUATE USE OF IRRATIONAL FIXED DRUG COMBINATIONS - K., Sudhakar; Latha, C. Deepa; Baloju, Deepika; Malahat, A. R.; Vijayalakshmi, G. (International Journal of Current Pharmaceutical Research, 2017)
Objective: To identify fixed drug combinations causing the adverse drug reactions both rational and irrational. Methods: A prospective observational study was carried out over a period of 6 mo (between June 2016 to December 2016) to evaluate adverse drug reactions related to fixed drug combinations in a tertiary care teaching hospital using suspected adverse drug reaction reporting form. Results: A total number of 64 adverse drug reactions were reported during this period. Of the total adverse drug reactions reported, 27 (42%) were due to fixed drug combinations. 6 (28.5%) were serious and 21(71.5%) were non-serious. Causality was certain in 4 (14.8%) cases and probably in remaining 23 (85.2%) cases. 19(70%) irrational fixed drug combinations were reported. Conclusion: The above results show that irrational fixed drug combinations contribute major extent to adverse drug reactions. Hence, awareness programs should be conducted for all the health care workers to improve the rationality of prescription and to decrease adverse drug reactions.